Analysis Of The Implementation Of A Portable Data Terminal (PDT)-Based Warehouse Management System In Increasing Warehouse Productivity And Cost Efficiency At XYZ Company - Irsyad Thalib Abdillah Irsyad Thalib Abdillah; Ebi Suryana; Muhammad Ghalih Massaid Waryanto (CV. AFDIFAL MAJU BERKAH, 2026)
The Indonesian logistics industry is currently facing pressure to achieve operational efficiency due to the rapid growth of e-commerce. Many warehouses still rely on manual processes, leading to inventory inaccuracies and suboptimal distribution. This study aims to analyze the impact of implementing a Warehouse Management System (WMS) integrated with a Portable Data Terminal (PDT) on the operational performance of XYZ Company. Using a mixed-methods case study approach, data was collected through structured observations, interviews with 25 key personnel, and historical document analysis. This study used Current Value Stream Mapping to identify operational waste and measure performance through cycle time, lead time, and process cycle efficiency. The results showed that the implementation of WMS-PDT significantly improved operational performance, reducing incoming process cycle time by 62% and outgoing process time by 50%. Furthermore, this digital transformation successfully minimized wasteful waiting and motion time, resulting in a reduction in inventory costs of IDR 13.7 billion with a benefit-to-cost ratio of 3.25:1. The study concluded that the integration of PDT into the WMS provides a robust framework for real-time data capture, effectively improving operational accuracy and service levels. These findings provide a strategic roadmap for logistics companies to leverage digital technologies to increase competitiveness.